2022
DOI: 10.3389/fgene.2022.926984
|View full text |Cite
|
Sign up to set email alerts
|

Genetic instability-related lncRNAs predict prognosis and influence the immune microenvironment in breast cancer

Abstract: Genome instability is a hallmark of cancer, and the function of lncRNAs in regulating genomic stability has been gradually characterized. However, the prognostic value of lncRNAs related to genetic instability has not been found in breast cancer. Here we constructed a genetic instability-related lncRNA model including U62317.4, SEMA3B-AS1, MAPT-AS1, AC115837.2, LINC01269, AL645608.7, and GACAT2. This model can evaluate the risk and predict the survival outcomes of patients. Further analysis showed that the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recent research [39] has shown that LINC00675 overexpression can inhibit breast cancer cell proliferation, migration, and invasion, while depletion of LINC00675 has the opposite effect. Additionally, literature [40] predict LDAs was further substantiated through these case studies involving these three cancers.…”
Section: Cases Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent research [39] has shown that LINC00675 overexpression can inhibit breast cancer cell proliferation, migration, and invasion, while depletion of LINC00675 has the opposite effect. Additionally, literature [40] predict LDAs was further substantiated through these case studies involving these three cancers.…”
Section: Cases Studiesmentioning
confidence: 86%
“…Recent research [39] has shown that LINC00675 overexpression can inhibit breast cancer cell proliferation, migration, and invasion, while depletion of LINC00675 has the opposite effect. Additionally, literature [40] has demonstrated that GACAT2 is associated with breast cancer. Only one lncRNA candidate is labeled as 'Unknown', indicating a temporary lack of evidence supporting its association with breast cancer.…”
Section: Cases Studiesmentioning
confidence: 99%